2021
DOI: 10.1088/1674-1056/ac2f30
|View full text |Cite
|
Sign up to set email alerts
|

Continuous non-autonomous memristive Rulkov model with extreme multistability*

Abstract: Based on the two-dimensional (2D) discrete Rulkov model that is used to describe neuron dynamics, this paper presents a continuous non-autonomous memristive Rulkov model. The effects of electromagnetic induction and external stimulus are simultaneously considered herein. The electromagnetic induction flow is imitated by the generated current from a flux-controlled memristor and the external stimulus is injected using a sinusoidal current. Thus, the presented model possesses a line equilibrium set evolving over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…This is the main reason that extreme multistability is often discovered in some circuits and systems involving memory-circuit elements. Intriguingly, extreme multistability has also been discovered in some non-autonomous memristive circuits and systems that have time-varying equilibria [33][34][35][36]. For example, a non-autonomous memristive FitzHugh−Nagumo circuit with its equilibrium points transitioning between no equilibrium point and a line equilibrium set was built, and hidden extreme mulitstability was disclosed [34].…”
Section: Introductionmentioning
confidence: 99%
“…This is the main reason that extreme multistability is often discovered in some circuits and systems involving memory-circuit elements. Intriguingly, extreme multistability has also been discovered in some non-autonomous memristive circuits and systems that have time-varying equilibria [33][34][35][36]. For example, a non-autonomous memristive FitzHugh−Nagumo circuit with its equilibrium points transitioning between no equilibrium point and a line equilibrium set was built, and hidden extreme mulitstability was disclosed [34].…”
Section: Introductionmentioning
confidence: 99%
“…For normal cases, the nonlinear circuits and systems have several determined equilibrium points and their attractors are self-excited from unstable equilibrium points [20]. However, when having time-varying equilibrium [21][22][23] or line/plane equilibrium [19,[24][25][26][27], the nonlinear circuits and systems demonstrated the coexisting behaviors of infinitely many attractors, resulting in the emergence of special extreme multi-stability.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing the nonvolatile locally active memristor into the neural network model composed of three Hopfield neurons, Li et al [27] revealed the coexistence phenomenon of multiple stable modes. Considering the influence of electromagnetic induction and external stimulus, extreme multistability in the continuous non-autonomous memristive Rulkov model was discovered by Xu et al [28]. A new no-equilibrium HR neuron model with memristive electromagnetic induction proposed by Zhang et al [29], which breeds the interesting phenomenon of hidden homogeneous extreme multistability.…”
Section: Introductionmentioning
confidence: 99%